Secure state estimation for cyber physical systems with state delay and sparse sensor attacks. (3rd May 2021) - Zhang, Man; Lin, Chong
ABSTRACT: In this paper, the problem of secure state estimation for cyber physical systems (CPSs) with state delay and sparse sensor attacks is studied. An algorithm combining set cover approach and adaptive switching mechanism is proposed, which can realize off-line acquisition of candidate set and accurately locate the real attack mode. The contributions of this algorithm are that it can greatly reduce the search space, eliminate the impact of attacks on state estimation, improve the estimation speed and ensure the real-time performance of state estimation under the premise of effective estimation. The sufficient condition for the existence of the observer is obtained. Finally, the rapidity and effectiveness of the designed observer are verified by two examples.